PENGARUH UMUR PANEN TERHADAP SIFAT FISIK TEPUNG JAGUNG MANIS (Zea mays saccharata Sturt) - Irawan, Fredy; Sumual, Maria F.; Pontoh, J. (Fakultas Pertanian, Universitas Sam Ratulangi, 2017)
Corn is a local food in Gorontalo Province which can be an alternative food. Processing of corn into flour is recommended, because it is more durable and easier to use for further processing. This study aims to determine age of sweet corn plants that can be processed into flour and physical characteristics at harvest age of 70, 80 and 90 days after plantation.This study used the method of Complete Randomized Design (CRD) with the treatments age of sweet corn at harvest i.e: 70, 80, and 90 days after plantation and 4 replications. Observed variable was the physical properties of sweet corn flour. Results showed that the averages of gelatinization temperature were ranged between 82 - 870C after 19.82 - 24.46 minutes and viscosity ranged 39.40% - 56.68%. Brightness level measured as L* value, were ranged between 64.5 - 70.4 and color measured as a* and b* values were ranged between 14.6 - 17.2 (redness) and 23.3 - 32.0 (yellowish), respectively. Water adsorption capacity of sweet corn flour were ranged between 55.15% - 71.73%, yield of corn rice were ranged between 94.10% - 98.63% and 66.98% - 76.99% of flour sweet corn. Age of sweet corn at harvest i.e : 70, 80, and 90 days after plantation can be prossed into flour while Physical properties showed no effect (viscosity and gelatinization temperature) however took effect in to color, water adsorbtion capacity and yield flour produced.